Effect of Inhaled Xenon on Cardiac Function in Comatose Survivors of Out-of-Hospital Cardiac Arrest—A Substudy of the Xenon in Combination With Hypothermia After Cardiac Arrest Trial. (29th July 2021) - Saraste, Antti; Ballo, Haitham; Arola, Olli; Laitio, Ruut; Airaksinen, Juhani; Hynninen, Marja; Bäcklund, Minna; Ylikoski, Emmi; Wennervirta, Johanna; Pietilä, Mikko; Roine, Risto O.; Harjola, Veli-Pekka; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: This explorative substudy aimed at determining the effect of inhaled xenon on left ventricular function by echocardiography in comatose survivors of out-of-hospital cardiac arrest. DESIGN: A randomized two-group single-blinded phase 2 clinical drug trial. SETTING: A multipurpose ICU in two university hospitals. PATIENTS: Of the 110 randomized comatose survivors after out-of-hospital cardiac arrest with a shockable rhythm in the xenon in combination with hypothermia after cardiac arrest trial, 38 patients (24–76 yr old) with complete echocardiography were included in this study. INTERVENTIONS: Patients were randomized to receive either inhaled xenon combined with hypothermia (33°C) for 24 hours or hypothermia treatment alone. Echocardiography was performed at hospital admission and 24 ± 4 hours after hypothermia. MEASUREMENTS AND MAIN RESULTS: Left ventricular ejection fraction, myocardial longitudinal systolic strain, and diastolic function were analyzed blinded to treatment. There were 17 xenon and 21 control patients in whom echocardiography was completed. Clinical characteristics did not differ significantly between the groups. At admission, ejection fraction was similar in xenon and control patients (39% ± 10% vs 38% ± 11%; p = 0.711) but higher in xenon than control patients after hypothermia (50% ± 10% vs 42% ± 10%; p = 0.014). Global longitudinal systolic strain was similar in xenon and control patients at admission (–9.0% ± 3.8% vs –8.1% ± 3.6%; p = 0.555) but better in xenon than control patients after hypothermia (–14.4.0% ± 4.0% vs –10.5% ± 4.0%; p = 0.006). In patients with coronary artery disease, longitudinal strain improved in the nonischemic myocardial segments in xenon patients. There were no changes in diastolic function between the groups. CONCLUSIONS: Among comatose survivors of a cardiac cause out-of-hospital cardiac arrest, inhaled xenon combined with hypothermia was associated with greater recovery of left ventricular systolic function in comparison with hypothermia alone.